Ensino da matemática na educação infantil : uma análise das percepções de professores e dos jogos de linguagem presentes em sua prática docente - Fredrich, Luciane Santorum (2018)
This research aims to analyze the language games used in the teaching practice of Mathematics teachers in Children's Education. Therefore, it seeks to identify the motivations of certain teachers to teach Mathematics in Children's Education and their relationships with mathematics and the language used in the classroom. The survey participants were fifteen teachers from a municipal school in the metropolitan area of Porto Alegre, Rio Grande do Sul. As data collection instruments, a questionnaire answered by the teachers and observations occurred at a time when mathematics activities were being carried out in the classes of the researched teachers. The answers given by the teachers were analyzed qualitatively with inspiration in the method of Discursive Textual Analysis (MORAES; GALIAZZI, 2011), relating them to the issues observed in the classroom. The theoretical contributions that served as the basis for this research were authors such as Fazolo (2014), Kramer (1994; 2006); Duhalde and Cuberes (1998), Smole (2000), Smole, Diniz e Cândido (2000), Lorenzato (2011), Dante (1996; 1998; 2010), Azevedo and Passos (2014), Nacarato, Mengali and Passos (2009), Garcia (1999) among others. Theoretically, for the realization of this analysis, it was sought to address some essential concepts from the studies of Wittgenstein (2014), Condé (1998), Gottschalk (2004; 2007), Bello (2010), Bannel (2013), D‟Ambrosio (2001), Lara (2001; 2011) among others. From the analysis of perceptions and feelings in relation to Mathematics and teaching in the Children's Education of the teachers participating in the research, seven categories emerged: Feelings involving family; Necessity to work; Experience of the teacher before, during and after training; Children's Education: the phase of discoveries and their enchantments; Playful activities such as Mathematics teaching strategies; Characteristics of the teacher of Children's Education; Teaching passion for Children's Education. In relation to the language games used in the teaching of Mathematics in Children's Education is portrayed the Mathematical approach, the Mathematical languages accessible to children and the language used during the classes, being possible to verify that the language that It has been used by teachers who teach Mathematics in Children's Education is the language used in the daily school, often at specific times of routine, like for example on the rounds of conversation. Moreover, it shows that the training of teachers who teach Mathematics in Children's Education does not approach mathematical concepts profoundly. In addition, I concluded through the analysis of this data that the play, the jokes and the games, at this stage of child development, are the strategies most used by these teachers to teach Mathematics in Children's Education. Stands out the importance that the teacher shall be attentive when using language games that they think are appropriate for Children's Education, because in some cases may be appropriating incorrect terms or constituting an infantilized idea that can be considered fragile in the following years.